Cholesterol Accumulation in Livers of Indian Medaka, Oryzias dancena, Acclimated to Fresh Water and Seawater - Ranasinghe, Naveen; Lin, Chia-Hao; Lee, Tsung-Han (Frontiers in Marine Science, 2022)
Sterol regulatory-element binding proteins (SREBPs), sirtuin (SIRT1), and liver X receptor α (LXRα) play important roles in regulating cholesterol metabolism in mammals. However, little is known about the relationship between cholesterol metabolism and SIRT1, LXRα, and SREBP1 in fish. In addition, knowledge of the effects of salinity on hepatic cholesterol metabolism in euryhaline teleosts is fragmented. This study revealed that hepatic cholesterol content was significantly different between fresh water (FW)- and seawater (SW)-acclimated Indian medaka. Gene expression analysis indicated srebp-1, lxrα, and sirt1 transcripts were not affected by changes in ambient salinity. However, SREBP-1, but not LXRα and SIRT1 protein expression, was significantly induced in the liver of FW-acclimated medaka. When SREBP-1 Vivo-MO inhibited SREBP-1 translation, hepatic cholesterol content was predominantly downregulated in FW- and SW-acclimated medaka. This is the first study to show that SREBP-1 is involved in cholesterol biosynthesis in fish. Furthermore, SREBP-1 knockdown had different effects on the expression of hmgcr and fdps, which encode the key enzymes involved in cholesterol biosynthesis. This study further enhances our knowledge of cholesterol metabolism in the livers of euryhaline teleosts during salinity acclimation.